Flow Pulsation Characteristic of External Gear Pump and Analysis of Influencing Factor - Liangyi Shen; Lei Qu; Biao Shen (Jixie chuandong)
Based on the bench test of oil pump， the influence of pump outlet pressure on flow pulsation of external gear oil pump is analyzed. The results show that the flow pulsation coefficient of the oil pump decreased with the increase of pump outlet pressure. The effects of different teeth number， modulus， pressure angle and end clearance on flow pulsation of oil pump are investigated by method of theoretical derivation and simulation. The analysis showed that the modulus had no effect on the flow pulsation of oil pump. The analysis shows that the pressure angle， the number of different teeth and the end clearance are the main factors affecting the flow pulsation. The flow pulsation coefficient decreased gradually with the increase of pressure angle. Increasing the number of driving gear teeth and driven gear teeth are beneficial to reducing the flow pulsation coefficient and improving the flow pulse phenomenon of oil pump. Among them， the number of driving gear teeth has a great influence on the flow pulsation. The flow pulsation coefficient of the oil pump decreased with the increase of the end clearance.